Kemampuan Mahasiswa Program Studi Pendidikan Matematika FKIP Unsyiah Menyelesaikan Soal PISA Most Difficult Level - Rini Sulastri; Rahmah Johar; Said Munzir (Universitas Syiah Kuala, 2014)
To increase and improve PISA rankings (Programme for International of Student Assessment) of Indonesian students not only starts from the students, but also teachers and prospective teachers. The purpose of this study was to determine the ability of students as prospective teachers to solve problems of high-level PISA (most difficult) is level 5. This study was a descriptive study using a qualitative approach to describe the ability of each student in solving PISA question. The subjects were students taking the Teaching Mathematics I course of Mathematics Education Program FKIP Unsyiah. Data analysis in qualitative research based on the results of the data collection process in the form of field notes, documentation, and interviews. Assessment conducted on students' ability to solve problems using the PISA assessment rubric. Furthermore, the score obtained is converted into the interval level of ability. The results showed only one student (14,28 %) of the seven students who have an excellent ability to resolve the matter appropriately. Meanwhile, three students (42,85 %) experienced only a mistake on the problems at the problem of the distance down. However, the ability of the three students vary based on the accuracy of the analysis in solving aspects. For the third ability of other students (42,85 %) were still low due to the settlement of questions that do not quite right with the ability to be at sufficient levels. Based on the results of this study are expected each faculty can use international issues as a matter of PISA in learning, so that students get used to solve the problems of non-routine to improve their ability to understand and solve problems, which can contribute to the future of teaching practice.